(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Mammography is a widely used screening tool for breast cancer. While it has been shown to reduce mortality from breast cancer, its benefits and risks vary depending on the age group being screened. This paper aims to provide a comprehensive review of the benefits and risks of mammography screening specifically in women aged 40 to 49 years. The analysis includes statistical data, benefits in terms of early detection and mortality reduction, as well as the potential risks such as false positives, overdiagnosis, and radiation exposure.